Strategi Pengadaan Sumber Daya Manusia Dalam Upaya Meningkatkan Kualitas Mutu Pengajar di Asy-Syukriyyah Islamic School - Della Oktafiana; Dina Mushlihah; Rizky Hikmahda (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
In order to achieve a superior educational program goals, professional educators are needed and have a strong determination to change the future of the nation and prepare the right strategy in achieving it. The purpose of learning at school in the education program which is the final target is maximum learning outcomes. Therefore, human resources must be prepared that are managed effectively and efficiently. With a strategy, the human resource procurement will become easier and more measurable. From planning to recruiting human resources must have good standards so that all processes are directed, right on target and can be a guideline so that superior and highly competitive human resources are obtained and have high quality that can provide the best to students. Through this article we explain how “Human Resources Procurement Strategy in an Effort to Improve the Quality of Teachers at Asy-Syukriyyah Islamic School - Tangerang”.